Screensavers : for healthier digital kids - Tan, Marlene Yiting (2014)
This paper presents Screensavers, a public information campaign to nurture healthier digital kids, initiated by three final year students from Wee Kim Wee School of Communication and Information, Nanyang Technological University. Through reaching out to the primary target audience, parents with primary school children aged 6 to 12, and the secondary target audience, children aged 6 to 12 themselves, the campaign aims to educate its target audiences on effectively managing digital technology use.